2016
DOI: 10.1007/s10295-016-1793-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3-hydroxypropionate biosynthesis in vitro by partial introduction of the 3-hydroxypropionate/4-hydroxybutyrate cycle fromMetallosphaera sedula

Abstract: The chemical 3-hydroxypropionate (3HP) is an important starting reagent for the commercial synthesis of specialty chemicals. In this study, a part of the 3-hydroxypropionate/4-hydroxybutyrate cycle from Metallosphaera sedula was utilized for 3HP production. To study the basic biochemistry of this pathway, an in vitro-reconstituted system was established using acetyl-CoA as the substrate for the kinetic analysis of this system. The results indicated that 3HP formation was sensitive to acetyl-CoA carboxylase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, availability of the key precursor, malonyl-CoA, is generally limited for 3-HP synthesis because the compound is important for cellular synthesis of other important compounds such as ketones and fatty acids . Another challenge of 3-HPA synthesis is the rate-limiting step of this pathway, previously identified as the reaction of Mcr . Effects of Mcr and Msr on 3-HP production were investigated using in vitro assays and measurement of steady-state kinetics parameters of Mcr and Msr.…”
Section: Production Of Carbon Dioxide- and Methane-derived Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, availability of the key precursor, malonyl-CoA, is generally limited for 3-HP synthesis because the compound is important for cellular synthesis of other important compounds such as ketones and fatty acids . Another challenge of 3-HPA synthesis is the rate-limiting step of this pathway, previously identified as the reaction of Mcr . Effects of Mcr and Msr on 3-HP production were investigated using in vitro assays and measurement of steady-state kinetics parameters of Mcr and Msr.…”
Section: Production Of Carbon Dioxide- and Methane-derived Productsmentioning
confidence: 99%
“…704 Another challenge of 3-HPA synthesis is the rate-limiting step of this pathway, previously identified as the reaction of Mcr. 705 HP synthesis from the β-alanine pathway (Figure 61). These engineering efforts yielded a final titer of 665 mg/L 3-HP.…”
Section: Production Of Carbon Dioxide-and Methane-derived Productsmentioning
confidence: 99%
“…Attenuating the latter pathway leads to higher intracellular levels of malonyl-CoA, thus improving 3-HP production. The fatty acid synthesis was primarily inhibited by using cerulenin (Li et al, 2015;Lynch et al, 2011;Rogers and Church, 2016;Ye et al, 2016). Due to the cost of adding such an inhibitor to a fermentation broth, alternative approaches were proposed through genetic engineering (X.…”
Section: Optimizing 3-hp Production Through Metabolic Engineeringmentioning
confidence: 99%
“…Due to the cost of adding such an inhibitor to a fermentation broth, alternative approaches were proposed through genetic engineering (X. Lynch et al, 2011;Ye et al, 2016). Although the disruption of genes involved in central metabolism can improve the 3-HP yield, it was also observed that it can hinder cell growth (Ko et al, 2017;Lynch et al, 2011;Tokuyama et al, 2014).…”
Section: Optimizing 3-hp Production Through Metabolic Engineeringmentioning
confidence: 99%